Possibilities of Cultivating Edelweis with Stem Cuttings - Arif Aliadi; Ervizal A. M Zuhud; Edje Djamhuri (Department of Forest Resources Conservation and Ecotourism - IPB University, 1990)
Edelweis (Anaphalis javanica) is a flowering plant which lives naturally at the peak of Mt. Pangrango.The flowers of this rare plant are beautiful and many people are attracted to take it.The Edelweis has an ecological role, i.e. supplying food for several insect types which feed on nectar, the living place of several types of mosses and its root system form a mycorrhizae system with a fungus and its branches also function as the nesting place of several types of birds.This study has the objectives to seek the possibilities of Edelweis breeding through stem cuttings using the research plan of complete random factorial.From this study the following results has been obtained : the number of living cuttings after 16 weeks of planting are 153 cuttings out of 240 cuttings planted or it amounts to 63.75%.